The standard treatment protocol for paracetamol poisoning may be inadequate following overdose with modified release formulation: a pharmacokinetic and clinical analysis of 53 cases. (2nd January 2018) - Salmonson, Heléne; Sjöberg, Gunilla; Brogren, Jacob
Abstract: Objective: The use of the standard procedure for managing overdoses with immediate release (IR) paracetamol is questionable when applied to overdoses with modified release (MR) formulations. This study describes the pharmacokinetics of paracetamol and the clinical outcomes following overdoses with a MR formulation. Methods: Medical records including laboratory analyses concerning overdoses of MR paracetamol from 2009 to 2015 were collected retrospectively. Inclusion criteria were ingestion of a toxic dose, known time of intake and documented measurements of serum paracetamol and liver function tests. Graphical analysis, descriptive statistics and population pharmacokinetic modelling were used to describe data. Results: Fifty-three cases were identified. Median age was 26 years (range 13–68), median dose was 20 g (range 10–166) and 74% were females. The pharmacokinetic analysis showed a complex, dose dependent serum versus time profile with prolonged absorption and delayed serum peak concentrations with increasing dose. Ten patients had persistently high serum levels for 24 h or more, six of them had a second peak 8–19 h after ingestion. Seven of 34 patients receiving N -acetylcysteine (NAC) within 8 h had alanine aminotransferase (ALT) above reference range. Three of them developed hepatotoxicity (ALT >1000 IU/l). Discussion and conclusions: The pharmacokinetic and clinical analysis showed that the standard treatment protocol, including risk assessment and NAC regimen, used for IR paracetamol poisoning not appear suitable for MR formulation. Individual and tailored treatment may be valuable but further studies are warranted to determine optimal regimen of overdoses with MR formulation.